2019
DOI: 10.1111/tpj.14599
|View full text |Cite
|
Sign up to set email alerts
|

A laser ablation technique maps differences in elemental composition in roots of two barley cultivars subjected to salinity stress

Abstract: Summary In saline soils, high levels of sodium (Na+) and chloride (Cl−) ions reduce root growth by inhibiting cell division and elongation, thereby impacting on crop yield. Soil salinity can lead to Na+ toxicity of plant cells, influencing the uptake and retention of other important ions [i.e. potassium (K+)] required for growth. However, measuring and quantifying soluble ions in their native, cellular environment is inherently difficult. Technologies that allow in situ profiling of plant tissues are fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…Rather, leaves rapidly shifted from early season transcriptional profiles to late season transcriptional profiles (Harris et al, 2021). However, current results suggest a unique elemental signature of veraison in "Cham- (Luo et al, 2016;Sardans et al, 2015), studies that compared sites without focus on environmental differences (Asaro et al, 2016;Shakoor et al, 2016), and studies that manipulated the plant's local environment (e.g., irrigation or salt treatments) (Chavarria et al, 2020;Shelden et al, 2020;Temme et al, 2019;Urbina et al, 2015). Often, effects from these studies tended to be with large influence from phylogeny (Neugebauer et al, 2018).…”
Section: Veraison Is a Middle-season Developmental Time Point In Grap...mentioning
confidence: 69%
See 1 more Smart Citation
“…Rather, leaves rapidly shifted from early season transcriptional profiles to late season transcriptional profiles (Harris et al, 2021). However, current results suggest a unique elemental signature of veraison in "Cham- (Luo et al, 2016;Sardans et al, 2015), studies that compared sites without focus on environmental differences (Asaro et al, 2016;Shakoor et al, 2016), and studies that manipulated the plant's local environment (e.g., irrigation or salt treatments) (Chavarria et al, 2020;Shelden et al, 2020;Temme et al, 2019;Urbina et al, 2015). Often, effects from these studies tended to be with large influence from phylogeny (Neugebauer et al, 2018).…”
Section: Veraison Is a Middle-season Developmental Time Point In Grap...mentioning
confidence: 69%
“…Our study builds on previous studies by examining leaf elemental composition with paired, real‐time features of the above‐ground environment. Most studies that have examined the influence of the environment on elemental composition have fallen into one of three categories: studies that analyzed large‐scale climatic features (such as annual rainfall) (Luo et al, 2016 ; Sardans et al, 2015 ), studies that compared sites without focus on environmental differences (Asaro et al, 2016 ; Shakoor et al, 2016 ), and studies that manipulated the plant's local environment (e.g., irrigation or salt treatments) (Chavarria et al, 2020 ; Shelden et al, 2020 ; Temme et al, 2019 ; Urbina et al, 2015 ). Often, effects from these studies tended to be variable with large influence from phylogeny (Neugebauer et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was possible to identify lines that showed high rates of root growth in both medium and high salinities, some due to having high levels of root growth in control conditions, such as Floye, and others despite not, such as Bere 49 A 27 Shetland. The latter of these are of most interesting as it has been shown that the maintenance of root elongation, in saline conditions that inhibit the normal shoot growth of the seedling, is indicative of an adaptive method to safeguard uptake of nutrients and water ( Shelden et al, 2020 ), with other experiments showing salinity tolerant lines having shorter roots in control conditions but maintaining them in saline conditions ( Adjel et al, 2013 ; Nefissi Ouertani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study builds on previous studies by examining leaf elemental composition with paired, realtime features of the above-ground environment. Most studies that have examined the influence of the environment on elemental composition have fallen into one of three categories: studies that analyzed large-scale climatic features (such as annual rainfall) (Sardans et al, 2015; Luo et al, 2016), studies that compared sites without focus on environmental differences (Asaro et al, 2016; Shakoor et al, 2016), and studies that manipulated the plant’s local environment (e.g., irrigation or salt treatments) (Urbina et al, 2015; Temme et al, 2019; Chavarria et al, 2020; Shelden et al, 2020). Often, effects from these studies tended to be variable with large influence from phylogeny (Neugebauer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%